Siloxane amide secondary amine chain extender as well as preparation method and application thereof
By using silicone alkylamide secondary amine chain extenders in the polyurethane system, the mechanical properties and degradability of polyurethane products are improved, the degradation problems caused by the residual of the hard segment of the polyurethane material are solved, and the release of harmful substances is avoided.
Patent Information
- Application Number
- CN202411779485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The residual structure of existing polyurethane materials in hard segments leads to incomplete decomposition and recycling, which cannot completely solve the problem of degradation of polyurethane products. In addition, traditional amine chain extenders will release harmful monomers during the decomposition and activation process, affecting the environmental protection of the products.
Silicone amide secondary amine chain extender is used as a slow reaction latent curing agent, which is stable in a single-component polyurethane system, and secondary reaction with water in the air can improve the maturation effect and mechanical properties, while degradation of the hard segment structure under certain external conditions.
The mechanical properties and overall degradability of polyurethane products are improved, the problem of release of harmful substances during decomposition of traditional latent curing agents is avoided, and the coordinated degradation of the hard and soft segments of polyurethane is achieved.
Smart Images

Figure BDA0005172430550000031 
Figure BDA0005172430550000032 
Figure BDA0005172430550000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyurethane, and specifically relates to a siloxane amide secondary amine chain extender and a preparation method and application thereof. Background Art
[0002] In the polyurethane system, chain extenders are used as functional additives, which can extend the polymer hard segment molecular chain to generate linear molecules with larger molecular weight, increase the hard segment content, and improve the overall mechanical properties of the product. Among them, amine chain extenders are an important type of high-performance chain extenders. Because of the urea bond generated by its reaction with isocyanate, it has excellent mechanical properties and forms a hydrogen bond structure between the chain segments, which improves the overall performance of the product. It is widely used in polyurethane coatings, polyurethane elastomers, polyurethane adhesives and other fields with high performance requirements.
[0003] Polyurethane is a cross-linked polymer material obtained by thermal curing of isocyanate and polyol. Polyurethane materials are widely used in many application fields due to their excellent properties. However, there are still some problems to be solved for polyurethane materials.
[0004] First, amines have high reactivity with isocyanates. Although adding amine chain extenders to the polyurethane system can effectively improve the performance of the product, if the type or amount of amine chain extenders is not appropriate, it will affect the operability of the system and even cause an explosion reaction. Especially in a one-component polyurethane system, amine chain extenders need to be used in the form of latent curing agents. Currently, most of them are ketimine or aldimine latent curing agents, but during the decomposition and activation process of such latent curing agents, harmful monomers will be released, affecting the environmental friendliness of the product.
[0005] At the same time, polyurethane materials themselves are non-degradable and cannot be recycled after being discarded, causing "white pollution". The current methods for dealing with polyurethane waste are mainly landfill and incineration, which will continue to cause different damages to the environment. Therefore, the development of environmentally friendly biodegradable polyurethane materials has become the key to the sustainable development of the industry in the future.
[0006] In recent years, the research on degradable polyurethane has become a hot topic of research. Patent CN115417964A discloses a degradable polyurethane, its preparation method, and a garden hose prepared therefrom. By adding lignin as a degradable component in the polyurethane system, a part of it provides a rigid aromatic group, which enhances the mechanical properties of the polymer, and at the same time provides an active hydrogen reaction site, which can replace part of the petroleum-based polyols, thereby forming a degradable polyurethane material. CN114133507A discloses a one-pot preparation method for bio-based degradable polyurethane. By using degradable butyrolactone as the polyurethane soft segment, the product is degradable and has good biocompatibility, which can be well applied in the packaging and biomedical fields.
[0007] The above patents use degradable materials in the soft segment structure and filler of the polyurethane system to improve the degradability of the product. However, the polyurethane system is composed of hard segment and soft segment structures. The residue of the hard segment structure will lead to incomplete decomposition and recycling of the product, and cannot completely solve the problem of polyurethane product degradation. Only when the soft and hard segment structures are degraded at the same time can the expected effect be achieved. Summary of the invention
[0008] The purpose of the present invention is to provide a siloxane amide secondary amine chain extender, which can be used as a slow-reacting latent curing agent, stably exist in a single-component polyurethane system, and improve the overall aging effect after use by secondary reaction with water in the air, thereby improving the mechanical properties of the product; in addition, the polyurethane product using the chain extender can also be decomposed under certain external conditions to achieve degradation of the polyurethane hard segment structure. In conjunction with other degradable soft segment structures, the overall degradability of the polyurethane product is further improved.
[0009] Another object of the present invention is to provide a method for preparing the siloxane amide secondary amine chain extender.
[0010] Another object of the present invention is to provide an application of the siloxane-based amide secondary amine chain extender.
[0011] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0012] A siloxane amide secondary amine chain extender, the structural formula of which is
[0013]
[0014] Among them, R1 is an aromatic ring or an aliphatic ring, preferably any one of a benzene ring, diphenylmethane, cyclohexyl, and dicyclohexylmethane; R2 is a C2-C10 alkyl group, preferably a C2-C5 alkyl group, and more preferably any one of an ethyl group, a propyl group, a butyl group, and a pentyl group.
[0015] In some specific embodiments, the structure of the siloxane amide secondary amine chain extender is as follows:
[0016]
[0017]
[0018] Wherein R2 is a C2-C10 alkyl group, preferably a C2-C5 alkyl group, more preferably any one of ethyl, propyl, butyl and pentyl.
[0019] Another aspect of the present invention provides a method for preparing the aforementioned siloxane amide secondary amine chain extender, comprising the following steps:
[0020] In the presence of a metal catalyst, one of a modified aromatic secondary amine monomer or a modified alicyclic secondary amine monomer reacts with a carboxyl-terminated siloxane monomer.
[0021] In some specific embodiments, the modified aromatic secondary amine monomer is selected from acrylonitrile-modified 4,4'-diaminodiphenylmethane Or acrylonitrile modified 1,4-phenylenediamine Any of .
[0022] In some specific embodiments, the alicyclic diamine monomer is selected from acrylonitrile-modified 4,4'-diaminodicyclohexylmethane Or acrylonitrile modified 1,4-cyclohexanediamine Any of .
[0023] In some specific embodiments, the carboxyl-terminated siloxane monomer is trimethoxysilyl acetic acid.
[0024] In some specific embodiments, the molar ratio of one of the modified aromatic secondary amine monomer or the modified alicyclic secondary amine monomer to the carboxyl-terminated siloxane monomer is 1:1-5.
[0025] In some specific embodiments, the metal catalyst is selected from one or more of zinc, bismuth, and tin, preferably bismuth and / or zinc, and more preferably zinc. The metal catalyst is preferably added in the form of metal powder to increase the contact area of the catalyst, preferably zinc powder.
[0026] In some specific embodiments, the amount of the metal catalyst is 0.1-1% of the sum of the weight of the modified aromatic secondary amine monomer or the modified alicyclic secondary amine monomer and the terminal carboxyl siloxane monomer, for example 0.1%, 0.3%, 0.5%, 0.7%, 1%, etc.
[0027] In some specific embodiments, the reaction temperature of the reaction is 50-150°C, for example, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, etc., and the reaction time is 1-5 hours, for example, 2 hours, 3 hours, 4 hours, etc.
[0028] Another aspect of the present invention provides a use of the siloxane amide secondary amine chain extender in the preparation of polyurethane.
[0029] The siloxane amide secondary amine chain extender of the present invention can be used alone or in combination with other chain extenders, and after being mixed with polyether and plasticizer, it can be used as a curing agent component for producing polyurethane related products. The related products can be applied to polyurethane coatings, adhesives and other fields.
[0030] Compared with the prior art, the beneficial effect of the present invention is that the chain extender of the present invention has a secondary amine group at one end and a siloxane group at the other end. Due to this special structure, the substance can be used as a latent curing agent in a polyurethane system. Specifically, the reaction process is divided into two parts. First, after mixing with isocyanate, the secondary amine group at one end reacts with isocyanate with appropriate activity to generate a urea bond and complete the initial chain extension reaction. Because the reaction activity of its secondary amine structure in the system is significantly lower than that of the primary amine structure, the reaction intensity at this stage is relatively mild, avoiding problems such as rapid heat release and significant increase in system viscosity. At the same time, its side chain structure modified with acrylonitrile can play an internal plasticizing role. Reduce the inter-segment force in the system and enhance the flexibility of the product. The siloxane group at the other end plays an end-capping protection role, does not react with the active substances in the system, temporarily delays the overall cross-linking reaction, and avoids the diamine / diol chain extender due to excessive activity causing the system to cross-link rapidly, resulting in rapid viscosity growth and gelation, affecting overall operability and stability. In the chain extension reaction of the first stage, due to the formation of urea bonds, it can be used as a rigid structure to improve the mechanical properties of the system. After the chain extension second stage is exposed to the air by brushing, the water in the air reacts with the siloxane group in the system, and the complete cross-linking of the macromolecular chain in the system is completed in a short time, reaching a complete aging effect, and the product performance can be quickly reached to a higher level. Therefore, the chain extender of the present invention is used as a kind of enhanced latent curing agent, while ensuring the stability of the system and significantly improving the system performance, rapid curing can be achieved when used, and harmful substances such as formaldehyde released when the traditional ketimine latent curing agent is unsealed are avoided.
[0031] The amide structure of the chain extender of the present invention can be decomposed under certain external conditions (for example, under alkaline conditions, the amide bond undergoes hydrolysis reaction at an ambient temperature of 60°C to 80°C to generate primary amine and carboxyl structures). That is, the hard segment is decomposed in the manner of the chain extender decomposition, and at the same time, the decomposition of polyester segments such as polylactic acid and polycaprolactone, i.e., the soft segment structure of polyurethane can be effectively promoted under the alkaline conditions, thereby achieving the decomposition of the hard segment and effectively promoting the degradation of the soft segment containing the polyester segment, thereby enhancing the overall degradation ability of the polyurethane product. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1-4 The following are the H NMR spectra of the products of Examples 1-4 respectively. DETAILED DESCRIPTION
[0033] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.
[0034] Some raw material sources:
[0035] Acrylonitrile modified HMDA, Beijing Bailingwei;
[0036] Acrylonitrile modified MDA, Beijing Bailingwei;
[0037] Acrylonitrile modified 1,4-cyclohexanediamine, Beijing Bailingwei;
[0038] Acrylonitrile modified p-phenylenediamine, Beijing Bailingwei;
[0039] Zinc powder, Umicore;
[0040] Bismuth isooctanoate catalyst, Umicore;
[0041] Dibutyltin dilaurate catalyst, Umicore;
[0042] MDI-50, from Wanhua Chemical Group Co., Ltd.;
[0043] C2020 polyether, from Wanhua Chemical Group Co., Ltd.;
[0044] F3135 polyether, from Wanhua Chemical Group Co., Ltd.;
[0045] 2-Trimethoxysilylacetic acid, Dow Corning;
[0046] Ketimine latent curing agent ALT-403, Changzhou Elite.
[0047] MDI system one-component coating: 200g C2020 polyether, 400g F3135 polyether, 350g 400 mesh calcium carbonate were stirred for 30min, and then dehydrated at 100℃ for 2 hours. The mixture was cooled to 80℃ and 165g MDI50 was added for polymerization reaction to generate MDI system one-component coating.
[0048] Other raw materials not specifically described in the examples of the present invention can be directly purchased from the market.
[0049] Example 1
[0050] (1) 1 mol of acrylonitrile-modified HMDA secondary amine and 1 mol of carboxyl-terminated siloxane are added to a dry reactor, and 0.02 mol of zinc powder catalyst is added, and the mixture is reacted at 50° C. for 1 hour. After distillation, a siloxane-based amide secondary amine latent curing agent is obtained.
[0051] (2) Add 18 g of the latent curing agent prepared in step (1) into 100 g of the MDI system single-component coating and stir for 20 min to ensure that it is evenly dispersed.
[0052] According to the national standard GBT19250-2013, the coating was applied twice at room temperature to finally obtain a 1.5mm thick standard mechanical properties test specimen. After curing at room temperature for 7 days, the mechanical properties test was carried out. The specimen was tested by a universal tensile machine within the tensile speed range required by the national standard. The tensile shear strength of the specimen can reach 4.5Mpa, and the elongation at break can reach 506%.
[0053] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml NaOH solution (pH=8.5), place it in an environment of 60±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 13.9%.
[0054]
[0055] The HMDA alicyclic peak is 1.6, the secondary amine peak is 3.3, and the siloxane peak is 3.55.
[0056] Example 2
[0057] (1) 2 mol of acrylonitrile-modified MDA and 10 mol of carboxyl-terminated siloxane were added to a dry reactor, and 0.012 mol of a bismuth catalyst was added, and the mixture was reacted at 150° C. for 5 hours. After distillation, a siloxane-based amide secondary amine latent curing agent was obtained.
[0058] (2) Add 18 g of the latent curing agent prepared in step (1) into 100 g of the MDI system single-component coating and stir for 20 min to ensure that it is evenly dispersed.
[0059] According to the national standard GBT19250-2013, the coating was applied twice at room temperature to finally obtain a 1.5mm thick standard mechanical properties test specimen. After curing at room temperature for 7 days, the mechanical properties test was carried out. The specimen was tested by a universal tensile machine within the tensile speed range required by the national standard. The tensile shear strength of the specimen can reach 5.3Mpa, and the elongation at break can reach 564%.
[0060] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml NaOH solution (pH=8.5), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 16.1%.
[0061]
[0062] The benzene ring NMR peaks are 6.5 and 7.0, the secondary amine peak is 7.3, and the siloxane peak is 3.5.
[0063] Example 3
[0064] (1) 3 mol of acrylonitrile-modified 1,4-cyclohexanediamine and 9 mol of carboxyl-terminated siloxane are added to a dry reactor, and 0.06 mol of a tin catalyst is added, and the mixture is reacted at 120° C. for 3 hours. After distillation, a siloxane-based amide secondary amine latent curing agent is obtained.
[0065] (2) Add 18 g of the latent curing agent prepared in step (1) into 100 g of the MDI system single-component coating and stir for 20 min to ensure that it is evenly dispersed.
[0066] According to the national standard GBT19250-2013, the coating was applied twice at room temperature to finally obtain a 1.5mm thick standard mechanical properties test specimen. After curing at room temperature for 7 days, the mechanical properties test was carried out. The specimen was tested by a universal tensile machine within the tensile speed range required by the national standard. The tensile shear strength of the specimen can reach 3.9Mpa and the elongation at break can reach 499%.
[0067] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml NaOH solution (pH=8.5), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 12.1%.
[0068]
[0069] The alicyclic peaks of cyclohexanediamine are 3.5, 2.7, and 1.4, the secondary amine peak is 3.3, and the siloxane peak is 3.5.
[0070] Example 4
[0071] (1) 4 mol of acrylonitrile-modified p-phenylenediamine and 16 mol of carboxyl-terminated siloxane were added to a dry reactor, and 0.16 mol of a tin catalyst was added, and the mixture was reacted at 108° C. for 2.5 hours. After distillation, a siloxane-based amide secondary amine latent curing agent was obtained.
[0072] (2) Add 18 g of the latent curing agent prepared in step (1) into 100 g of the MDI system single-component coating and stir for 20 min to ensure that it is evenly dispersed.
[0073] According to the national standard GBT19250-2013, the coating was applied twice at room temperature to finally obtain a 1.5mm thick standard mechanical properties test specimen. After curing at room temperature for 7 days, the mechanical properties test was carried out. The specimen was tested by a universal tensile machine within the tensile speed range required by the national standard. The tensile shear strength of the specimen can reach 4.1Mpa, and the elongation at break can reach 504%.
[0074] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml NaOH solution (pH=8.5), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 13.5%.
[0075]
[0076] The benzene ring peak is 6.67, the siloxane peak is 3.55, and the secondary amine peak is 6.76.
[0077] Comparative Example
[0078] 18g of ketimine latent curing agent was added to 100g of MDI system single-component coating, stirred for 30 minutes and fully mixed, and then brushed twice at room temperature according to the national standard GBT19250-2013 to obtain a 2.5mm thick standard mechanical properties test specimen. After curing for 7 days at room temperature, the mechanical properties test was carried out. The specimen was tested by a universal tensile testing machine within the tensile speed range required by the national standard, and the tensile shear strength was 3.1Mpa and the elongation at break was 510%.
[0079] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample, immerse it in 25ml NaOH solution (pH=8.5), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate is 2.3%.
[0080] It can be seen that the siloxane amide secondary amine chain extender of the present invention comprises a terminal secondary amine group, and the amine group can react with isocyanate to form a rigid urea bond, which has a significant improvement effect on the tensile strength, hardness and other mechanical properties of polyurethane products. Since the secondary amine activity is more moderate, the reaction activity of the system can be better controlled, so that its heat release and system viscosity are both within an appropriate range. The siloxane group at the other end can be stably present in the system, avoiding complete crosslinking of the macromolecular chain in the system, so that the chain extender is present in the system as a latent curing agent, ensuring that the system maintains good long-term stability before use. And when it is painted, the siloxane group therein contacts with water in the air and undergoes a crosslinking reaction quickly, so that the system is quickly shaped and cured. The construction efficiency is effectively improved. While this latent curing agent is stably present in a single-component polyurethane system, it effectively improves the curing efficiency and the mechanical properties of the product. The polyurethane product of this chain extender can also be decomposed under certain external conditions. Since the chain extender belongs to the hard segment of the polyurethane, the degradation problem of the polyurethane hard segment can be solved through its own degradation. It avoids the degradation of the polyurethane hard segment that can only be achieved by complex and high-cost modification of the isocyanate monomer. When used together with the degradable polyol component, it can achieve effective degradation in both the soft and hard segments, thereby improving the overall degradation ability of the polyurethane products.
Claims
1. A siloxane amide secondary amine chain extender, the structural formula of which is: in, R1 is an aromatic ring or an aliphatic ring, preferably any one of a benzene ring, diphenylmethane, cyclohexyl, and dicyclohexylmethane; R2 is a C2-C10 alkyl group, preferably a C2-C5 alkyl group, and more preferably any one of an ethyl group, a propyl group, a butyl group, and a pentyl group.
2. The siloxane amide secondary amine chain extender according to claim 1, characterized in that: The structure of the siloxane amide secondary amine chain extender is as follows: Wherein R2 is a C2-C10 alkyl group, preferably a C2-C5 alkyl group, more preferably any one of ethyl, propyl, butyl and pentyl.
3. A method for preparing the siloxane amide secondary amine chain extender according to claim 1 or 2, comprising the following steps: In the presence of a metal catalyst, one of a modified aromatic secondary amine monomer or a modified alicyclic secondary amine monomer reacts with a carboxyl-terminated siloxane monomer.
4. The method according to claim 3, characterized in that The modified aromatic secondary amine monomer is selected from acrylonitrile-modified 4,4'-diaminodiphenylmethane Or acrylonitrile modified 1,4-phenylenediamine Any one of; and / or, the alicyclic diamine monomer is selected from acrylonitrile-modified 4,4'-diaminodicyclohexylmethane Or acrylonitrile modified 1,4-cyclohexanediamine Any of .
5. The method according to claim 3 or 4, characterized in that: The carboxyl-terminated siloxane monomer is trimethoxysilyl acetic acid.
6. The method according to any one of claims 3 to 5, characterized in that: The molar ratio of one of the modified aromatic secondary amine monomer or the modified alicyclic secondary amine monomer to the carboxyl-terminated siloxane monomer is 1:1-5.
7. The method according to any one of claims 3 to 6, characterized in that: The metal catalyst is selected from one or more of zinc, bismuth and tin, preferably zinc and / or bismuth, more preferably zinc powder.
8. The method according to any one of claims 3 to 7, characterized in that: The amount of the metal catalyst used is 0.1-1% of the total weight of the modified aromatic secondary amine monomer or the modified alicyclic secondary amine monomer and the carboxyl-terminated siloxane monomer.
9. The method according to any one of claims 3 to 8, characterized in that: The reaction temperature is 50-150°C and the reaction time is 1-5 hours.
10. Use of the siloxanylamide secondary amine chain extender according to claim 1 or 2 or the siloxanylamide secondary amine chain extender prepared by the method according to any one of claims 3 to 9 in the preparation of polyurethane.
Citation Information
Patent Citations
One-pot preparation method of bio-based degradable polyurethane
CN114133507A
Degradable polyurethane, preparation method thereof and garden water pipe prepared from degradable polyurethane
CN115417964A
Secondary amine chain extension cross-linking agent and polyurethane elastic material
CN114044869A
Hydroxyl-containing bis-secondary amine as well as preparation method and application thereof
CN115215755A
N,N'- and N,N',N'-substituted silylureas and process for their production
US4623740A